A comparison of slides used in patient handling - Dockrell, Sara (My University, 2001)
Patient-handling slides are the most recently introduced moving and handling aid. At present, there is little research-based information available on their use. This study compared four slides currently used in patient moving and handling. Two tasks were performed with each slide, and the ease of learning how to use them and the ease of use of each slide was evaluated.
PUBLISHED
Keywords: Patient-handling slides; Patient moving; Patient handling